EVALUASI KINERJA PEMERINTAH DESA DALAM PENGGUNAAN ALOKASI DANA DESA DI DESA PERET KECAMATAN DAMAU KABUPATEN KEPULAUAN TALAUD - Tatibi, Yolanda Deisye; ROMPAS, WELSON; KOLONDAM, HELLY FEBRINA (Sam Ratulangi University, 2017)
This research focuses on the implementation of conceptual accountability management in village financial matters andaims to describe government’s involvements in transitioning to or consolidating better establishment for the citizens. Thisstudy is conducted due to funds allocation management by the Village Budget Committee is fairly administered and yetagainst the law. Therefore, this research can confidently be beneficial not only to Talaud Regency, but also Damau districtin terms of improving the accountability of village financial administration.This research is executed at Peret Village, Damau district. The informants are citizen and the village committeeswho are advised to be competent in representing the survey unit in the management of village financial allocations. Thisresearch uses both qualitative and quantitative method which emphasise on the contextual research includes ethnographictechniques such as direct participants observations and interviews which are designed to capture different judgement andperceptions.Furthermore, this research will show that planning and implementation management of village fund allocation canestablish better accountability management for the local government. Despite the implementation of such accountabilityhas been shown successful, its management has yet been properly administered. Thus, its regulation and members dorequire further guidance. Moreover, the main concern is the inefficiency as well as the lack of setting priorities apparatusand human resources reforms hence the needs for assistances from the local government apparatus in a sustainablemanner.Keyword: Village Financial Allocations, Performance, Evaluation